Heterogeneous Polypropylene-Based Cation-Exchange Membrane Modified by Functionalized Zinc Oxide Particles for Vanadium Redox Flow Battery - Khoiruddin, Khoiruddin; Firmansyah, Rizky W.; Yulanda, Nanda; Wardani, Anita K.; Wenten, I Gede (Reaktor, 2024)
This work presents the synthesis and characterization of heterogeneous cation-exchange membranes based on polypropylene (PP) and cation-exchange resin (IER) powder, developed via melt spinning. The membranes were modified with zinc oxide (ZnO) nanoparticles functionalized with polydopamine (PDA) to enhance their electrochemical properties. The effects of varying IER content and ZnO/PDA loading on key membrane properties, including ion-exchange capacity (IEC), water uptake (WU), water contact angle (WCA), proton conductivity, water permeability, and vanadium permeability, were systematically investigated. The results demonstrated that increasing IER content improved proton conductivity and IEC, but also increased vanadium permeability. The PP/ZnO-PDA (Z-2.5) membrane, with 2.5%-wt. ZnO/PDA, showed reduced water permeability (0.46 L·m⁻²·h⁻¹·bar⁻¹) and vanadium permeability (5.67 × 10⁻⁵ cm² min⁻¹), while maintaining moderate proton conductivity (13.17 mS/cm). However, increasing ZnO/PDA content beyond 2.5%-wt. led to declines in WU, IEC, and proton conductivity, likely due to nanoparticle aggregation reducing access to ion-exchange sites.